Acácio Gil Borsoi: arquitetura residencial paraibana - Melo, Marieta Dantas Tavares de (2013)
This research intends to initiate an in-depth analysis process of the single-family residential architecture produced, in the state of Paraiba, by the architect Acácio Gil Borsoi, who was born in Rio de Janeiro, with emphasis on the period between 1953 and 1979, which marks the period of construction of the selected houses. According to Acácio Gil Borsoi, the house is, primarily, a program that made the architectural experimentation possible for him; it plays an essential role in his career, so much so that it is the architect s most recurrent program. From the observation of eight selected examples in Paraiba, it is expected that through the drawings based on analytical parameters specific and recurring aspects of the analyzed projects are revealed. This study aims to identify the architectural features in the set of singlefamily residential buildings designed by Acácio Gil Borsoi s in Paraiba, and compare them with general characteristics attributed to his projects by two of the most relevant pieces of work about him.